ОБЩЕЕ ВОПРОСЫ ПРЕПОДАВАНИЕ ГРАММАТИКИ ИНОСТРАННЫХ ЯЗЫКОВ (Scientific journal of the Fergana State University, 2023)
The article focuses on scientific and pedagogical analysis of the theoretical and methodological foundations of teaching gramatics of foreign languages. The german family in the category of foreign languages, where the possibilities of the formation of the grammatical meaning of a word on the example of English in this place were carried out through a cognitive analysis, from the results of which Universal conclusions on this topic were developed.